The Transition According to Cambridge, Mass. - Murrell, Peter; Haltiwanger, John; Schrenk, Martin (Journal of Economic Literature, 2015)
This paper reviews the NBER's "The Transition in Eastern Europe." This book's 18 essays examine privatization, stabilization, fiscal policies, the nascent private sector, bankruptcy, foreign trade, and investment, etc. Individual country performance occupies six studies. These essays, which are of high quality, provide a cross-section of the literature on transition. However, the book's stronger conclusions are not supported by strong evidence. Two conclusions, unemphasized by contributors, emerge. Expectations, which reflect the theories used to design standard reforms, are often unfulfilled during reforms. A plausible explanation for the misplaced expectations is the ahistorical approach of those theories.